Nonsurgical Management of Nifedipine Induced Gingival Overgrowth - George Sam; Staly Chakkalakkal Sebastian (Case Reports in Dentistry)
Drug-induced gingival overgrowth is frequently associated with three particular drugs: phenytoin, cyclosporin, and nifedipine. As gingival enlargement develops, it affects the normal oral hygiene practice and may interfere with masticatory functions. The awareness in the medical community about this possible side effect of nifedipine is less when compared to the effects of phenytoin and cyclosporin. The frequency of gingival enlargement associated with chronic nifedipine therapy remains controversial. Within the group of patients that develop this unwanted effect, there appears to be variability in the extent and severity of the gingival changes. Although gingival inflammation is considered a primary requisite in their development, few cases with minimal or no plaque induced gingival inflammation have also been reported. A case report of gingival overgrowth induced by nifedipine in a patient with good oral hygiene and its nonsurgical management with drug substitution is discussed in this case report.